Combination of phage display and molecular grafting generates highly specific tumor-targeting miniproteins - Zoller, Frederic; Markert, Annette; Zhao, Wenye; Weichert, Wilko; Askoxylakis, Vasileios; Altmann, Annette; Mier, Walter; Haberkorn, Uwe (Angewandte Chemie. International edition, 2012)
Frankenstein′s peptide: The grafting of the binding domain from miniprotein Min-23 into the sunflower trypsin inhibitor (SFTI-I) peptide scaffold (see scheme) preserved its in vitro and in vivo binding specificity and proteolytic stability. The combination of these peptides was shown to be tumor-specific with a good binding affinity for delta-like ligand 4 (Dll4) protein. The use of SFTI-I as a peptide scaffold is ideal for hit-to-lead development.